EFFECTS OF THE USE OF TABLE TENNIS IN SPORTS THERAPY IN PSYCHIATRIC HOSPITALS. CASE STUDY: PATIENT WITH ALCOHOL DEPENDENCE (University Arena, 2025)
Sports therapy is an effective scientific method of supporting specialized psychiatric treatments. By using sports therapy in psychiatric medical treatment, the patient's physical and mental health is improved. Research to date shows that in psychiatric clinics where patients also benefit from sports therapy, the recovery process is accelerated. Patients' access to a gym and/or possibly to aswimming pool improve sports therapy, making it possible to carry out therapy regardless of the season or weather. The most common sports in sports therapy are: table tennis, swimming, badminton, basketball, volleyball, fitness, walking and running outdoors, yoga, cycling or even climbing on special boards. Table tennis is an accessible and effective method to support psychiatric therapy, having effects on the patient's mental health through a combination of physical exercise, cognitive stimulation and social interaction. By accepting the regular practice of table tennis, an acceleration of the rehabilitation process is observed in patients with alcohol dependence. At the cellular level, following the moderate physical effort of table tennis, there is a substantial release of endorphins and the level of cortisol in the blood is regulated, which leads to a decrease in stress levels and an increase in the patient's ability to concentrate and disconnect from anxious thoughts. After analyzing the results of the conducted experiment it can be concluded that the first and easiest method of sports therapy in psychiatric clinics is table tennis. It proves the hypothesis that table tennis significantly helps the patient with alcohol addiction problems to quickly regain body and mental control in comparison with the patient who does not want or does not have the possibility to participate in sports therapy sessions. The patients with alcohol dependence contact with the gym, with the rules of table tennis and with other players helps in better managing their emotions, improves self-esteem, encourages physical movement and social contact and also demonstrates the importance of sport therapy.
Keywords: table tennis; psychiatric; sports therapy; alcohol; dependence